DROUGHT-INDUCED TRANSCRIPTION OF RESISTANT AND SENSITIVE COMMON MILLET VARIETIES - R. Y. Wang; H. G. Wang; X. Y. Liu; S. Lian; L. Chen; Z. J. Qiao; C. E. McInerney; L. Wang (Journal of Animal and Plant Sciences, 2017)
As a well-adapted plant to dry soil and short growing seasons, common millet holds great potential as a drought-resistant crop. Here, we performed a comparative RNA-Seq analysis of two common millet genotypes, Huangmizi (tolerant) and Zhenyuandamizi (sensitive) grown under stress conditions (20% Polyethylene Glycol 6000 with an average molecular weight of ～5,400-7,000 solution). Leaves of seedling plants were harvested from a control and also after 1 and 3 h stress treatment and pooled for RNA isolation. Using Illumina paired-end sequencing, approximately 46.5 million clean reads were generated. Following a de novo assembly, a total of 42,240 Unigenes were obtained. A total of 2,301 SSRs and 1,447,148 SNPs were also identified and 75% of Unigenes were annotated. A total of 21,556 and 8,304 Unigenes aligned to the GO and COG databases, respectively. The GO classification showed that the Unigenes were distributed into three categories with 74.30% having biological functions, 76.51% having molecular functions and 79.30% having cellular-level functions. By cross-referencing against KEGGs, 5,535 Unigenes were assigned to 63 metabolic pathways. Additionally, 701 DEGs including 187 up-regulated and 514 down-regulated genes were detected. Transcripts identified in this study will accelerate our understanding of the molecular mechanisms of drought tolerance in common millet.
Keywords: Common millet (Panicum miliaceum L.); Drought; Transcription